2018
DOI: 10.3892/ol.2018.8006
|View full text |Cite|
|
Sign up to set email alerts
|

Anthelmintic pyrvinium pamoate blocks Wnt/β-catenin and induces apoptosis in multiple myeloma cells

Abstract: Abstract. Multiple myeloma (MM) is a malignancy of the bone marrow. The median survival time of patients with MM is only 5 years, with patients frequently experiencing relapse. Currently, there is no effective therapy for recurrent MM. The results of the present study indicated that pyrvinium pamoate (PP), a US Food and Drug Administration-approved oral anthelmintic drug, exhibited potent antitumor activity in MM cells in vitro. It is demonstrated that PP inhibited MM cell proliferation and mediated apoptosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Treatment of both the HMCL RPMI-8226 as well as primary MM cells with PP resulted in an increase in apoptosis. Combinatorial treatment with Bortezomib was also reported in this study to result in a synergistic effect on MM cell viability [ 142 ]. Although the results of these and many other studies are hopeful, challenges for moving these drugs towards treatment of MM lie ahead.…”
Section: The Wnt Pathway As a Potential Therapeutic Target In Multiplsupporting
confidence: 54%
“…Treatment of both the HMCL RPMI-8226 as well as primary MM cells with PP resulted in an increase in apoptosis. Combinatorial treatment with Bortezomib was also reported in this study to result in a synergistic effect on MM cell viability [ 142 ]. Although the results of these and many other studies are hopeful, challenges for moving these drugs towards treatment of MM lie ahead.…”
Section: The Wnt Pathway As a Potential Therapeutic Target In Multiplsupporting
confidence: 54%
“…Moreover, inhibition of Wnt signaling by ectopic expression of a dominant negative TCF4 mutant (dnTCF4) in HMCLs suppressed proliferation, implying functional involvement of β-catenin/TCF-mediated transcription. Corroborating these results, other studies showed that siRNA [33] and shRNA [34] mediated silencing of β-catenin or treatment of HMCLs with the small molecule Wnt/β-catenin inhibitors PKF115-584 [35], AV-65 [36], BC2059 [37], CGK012 [38], and the FDA-approved Pyrvinium pamoate [39, 40] attenuated cell cycle progression, impaired tumor growth, and markedly increased apoptosis of HMCLs both in vitro and in vivo. In addition to attenuating proliferation, silencing of β-catenin increased the sensitivity of the tumor cells to multiple drugs used in the treatment of MM, in particular to lenalidomide [34, 41].…”
Section: Aberrant Canonical Wnt Signaling In MM Cellsmentioning
confidence: 89%
“…First, pyrvinium inhibits canonical Wnt signaling pathway by β-catenin degradation in multiple myeloma. Secondly, pyrvinium impairs mitochondrial functions in multiple hematological malignancies [14 , [22] , [23] , [24] , [25] . Here, we investigated both possible mechanisms to identify how pyrvinium exerts its anti-leukemic effects in AML cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have described two mechanisms by which pyrvinium exerts its anti-neoplastic effects. Pyrvinium is able to inhibit the canonical Wnt signaling pathway via β-catenin degradation, but can also impair mitochondrial respiration [14 , [22] , [23] , [24] , [25] . As our data showed a lack of β-catenin expression in MLL -rearranged AML cells, it is unlikely that pyrvinium affected Wnt signaling in these cells.…”
Section: Discussionmentioning
confidence: 99%